Experiments in Decolonizing the University : Towards an Ecology of Study - Schildermans, Hans (Bloomsbury Academic)
Explores the relation between university and society by taking study practices as a point of departure.
English
Keywords: Philosophy & theory of education; Higher & further education, tertiary education